Implementation of pancasila student profile in vocational high school students - Andri, Andriyanto; Handoyono, Nurcholish Arifin; Widodo, Widodo (Universitas Sarjanawiyata Tamansiswa, 2024)
The current students are increasingly moving away from the values of Pancasila. Many misbehaviors are happening that cause students to deviate from the values in line with Pancasila. Therefore, the implementation of the Pancasila Student Profile is very important to be applied in schools. The objectives of this research are: (1) to describe the process of implementing the Pancasila Student Profile in vocational schools; (2) to determine the character of vocational school students towards the Pancasila Student Profile. This research is a qualitative study of the case study type. The data sources in this study are primary and secondary data. Data collection techniques include observation, interviews, and documentation. Data validity is ensured through data source triangulation and methods. Data analysis techniques include data reduction, data presentation, conclusion drawing, and verification.The research results show that: (1) The process of implementing the Pancasila Student Profile in the learning of 10th-grade students in Light Vehicle Engineering at An Nur Banjarejo Vocational School is carried out in two different stages. In the first stage, it is conducted during the P5 learning with an allocation of 288 hours per year or 144 hours per semester and is implemented in a block system. (2) The character of 10th-grade students in Light Vehicle Engineering at An Nur Banjarejo Vocational School towards the Pancasila Student Profile already strongly reflects students who uphold the noble values of Pancasila. The impact of this character improvement is that students become more disciplined, independent, and responsible for their tasks.